(untitled) (Nonconventional Technologies Review, 2024)
The study undertaken addresses the possibility of making a device for analyzing the way in which the plasticization parameters of the materials in the injection process. The analysis is carried out both from a dimensional point of view, but also from the point of view of the deformations that may appear in the injection assembly during its production process. The geometrical change of the dimensions of the active elements in the analyzed process is also analyzed. It can be seen that the active elements undergo a slight ovalization process along the directions of the X-Y plane at the piston of the order of microns, and at the compression cylinder also of the order of microns.